Using Traditional Ecological Knowledge to Develop Closure Criteria in Tropical Australia - Smith, HD (Mine Closure 2008: Third International Seminar on Mine Closure, 2008)
The Northern Land Council is one of a number of similar statutory bodies created by the Australian Federal Government upon implementation of the Aboriginal Land Rights Act in 1976. One of its more important functions is to act as a land manager on behalf of Australian Aborigines living in the northern part of Australia’s Northern Territory on Aboriginal freehold land. The ultimate and desirable outcome for rehabilitating exhausted mines is to leave the affected land in a state that has future value for use by subsequent generations. For companies to meet this goal, and ensure that stakeholder satisfaction is obtained, consultation with land owners prior to mine closure is essential. Although best practice now dictates that planning for closure should be undertaken at the commencement of the mining phase, this was often not done and represents a problem for older mines now facing closure. This paper describes practical means that have ensured effective consultation and achieved acceptable levels of stakeholder satisfaction. Achieving stakeholder satisfaction requires that traditional ecological knowledge is included in the mine closure process. Results demonstrate that both aboriginal and non-Aboriginal people perceive that there is a role for traditional ecological knowledge, not only for development of closure criteria, but throughout the environmental impact assessment process. A means by which this information can be obtained in a culturally sensitive manner, and used in conjunction with western science to achieve a mutually acceptable long-term outcome for mine rehabilitation, is presented. Outcomes are compared to those from systems in place in Canada and New Zealand, and barriers to success in Australia are discussed.